Change in the Length of the Vegetation Period of Tomato (Solanum lycopersicum L.), White Cabbage (Brassica oleracea L. var. capitata) and Carrot (Daucus carota L.) Due to Climate Change in Slovakia - Ján Čimo; Elena Aydın; Karol Šinka; Andrej Tárník; Vladimír Kišš; Peter Halaj; Lucia Toková; Tatijana Kotuš (Agronomy, 2020)
Climate change is affecting all sectors of human activities worldwide, including crop production. The aim of the paper was to evaluate the average daily air temperatures measured at one hundred meteorological stations across Slovakia in 1961–2010 and calculate the maximum length of the vegetation period for Solanum lycopersicum L., Brassica oleracea L. var. capitata and Daucus carota L. Future trends predictions of the temporal and spatial development across the duration of the vegetation period in Slovakia were elaborated for decades 2011–2020, 2041–2050, 2071–2080 and 2091–2100. Our results show that there was an earlier start to the vegetation period in spring and a later termination in autumn for past 30 years. There is a predicted trend of prolongation of the maximum duration of the vegetation period up to 20 days (Solanum lycopersicum L., Brassica oleracea L. var. capitata) and 15 days (Daucus carota L.) in comparison with the refence decade 2001–2010. The maximum vegetation period duration will extend from the south of Slovakia towards the north of the country. The predicted potential increase in crop vegetation periods will be limited by other constraints such as the availability of arable land and soil water availability.